MP18: Pre-departure and post-elective requirements for global health electives: a survey of Canadian Royal College emergency medicine programs. (May 2020) - Pritchard, J.; Collier, A.; Bartels, S.
Abstract : Introduction: Participation in Global Health (GH) electives can improve resourcefulness, cultural and ethical insight, and personal development. Risks to trainees, hosts and institutions may be minimized through pre-departure and post-elective training. In 2016 such training was mandatory in only 3 Canadian residency programs, however there is no published data specific to Canadian Emergency Medicine (EM) programs. This study sought to identify current GH elective requirements and related perceived gaps among Royal College EM programs. Methods: We conducted two cross-sectional surveys in 2019 (one each for Royal College EM PDs and residents) via email regarding training requirements for GH electives. Additionally, a survey link was distributed in the CAEP EM resident newsletter. We also contacted university PGME and/or global health offices to understand and collate university-wide requirements and resources. Results: Nine PDs responded, with 78% reporting having 1-5 residents participate in GH electives yearly. Many PDs were unsure of the requirements surrounding GH electives; two reported that pre-departure training was required, while none reported requiring post-departure debriefs. Overall, 67% of PDs felt that their residents were moderately prepared for GH electives and 33% felt they were unprepared to some degree. Thirty-three percent believed that improvements should be made to either pre-departure training or both pre- and post-departure training, while 56% were unsure if improvements were needed. Forty-seven out of an estimated 380 residents responded. Thirty-five percent of residents had completed a GH elective during residency. Of residents who participated in a GH elective, only one (6%) reported feeling very prepared; 18 residents (43%) reported there was a need to improve trainings. Residents reported a number of challenges during electives (lack of resources, inadequate supervision, safety issues) and identified priority topics for training. Conclusion: Although EM residents are participating in GH electives, the majority of EM residency programs do not require pre- or post-departure training. Some PDs and residents report varying levels of preparedness, and residents acknowledge a variety of challenges during GH electives. This information can be used to inform pre-departure/post-elective GH training or to encourage EM residents to access university-wide training.